Asbestos related pleuropulmonary lesions and the erythrocyte sedimentation rate. Issue 10 (October 1984) - Hillerdal, G
Abstract : Asbestos related lesions of the lung parenchyma and the pleura can be divided into three main types: parietal pleural plaques, diffuse interstitial fibrosis ("classical asbestosis"), and a third type of reaction affecting both the pleura and the lung parenchyma. The last type includes such lesions as acute pleurisy, diffuse pleural thickening, and rounded atelectasis. Among 1344 patients with asbestos related pleural lesions, 1190 had pleural plaques, 29 of whom also had pulmonary fibrosis (asbestosis); 83 had unilateral sequelae of pleurisy, of whom nine had asbestosis; and 71 had bilateral sequelae of pleurisy, of whom 23 also suffered from asbestosis. The erythrocyte sedimentation rate (ESR) was measured in 184 patients--79 with pleural plaques, 44 with unilateral sequelae of pleurisy, and 61 with bilateral sequelae. In patients with pleural plaques with or without asbestosis the ESR was usually normal, the mean being 9.6 mm in one hour. Among patients with sequelae of pleurisy, however, many had a raised ESR. The mean ESR was 25.7 mm in one hour in those with bilateral changes and 13.2 in those with unilateral changes. Statistical analysis showed that in this group of subjects the presence of sequelae of pleurisy was a highly significant determining factor for the ESR (p less than 0.0001). Asbestosis alone was not a significant determining factor but there was a low grade of significance for the combined effect of asbestosis and sequelae of pleurisy (p less than 0.05). These findings suggest that the pathogenesis of the various changes is different.